A Cross Sectional Study on Knowledge and Attitudes About Organ Donation and Transplantation in an Urban Population in a Low-Income Country - Kituuka, Olivia; Ocan, Moses; Mbiine, Ronald; Ibingira, Charles; Wayengera, Misaki; Tayebwa, Mordecai (Research Square, 2023)
Uganda’s Health Sector Development Plan (2015/16 -2019/2020) noted that most referrals for treatment abroad were for organ transplant services costing government over 5.6 million US dollars. The government of Uganda has invested in building capacity for Organ donation and transplantation services by training human resource and setting up the infrastructure in Kampala where these services can be accessed. However, there is no information on the readiness of communities and the scientific community to embrace (communities) or undertake (science) organ transplantation in the country. We set out to assess Knowledge and Attitudes about organ donation and transplantation among the urban population in Kampala. Methods: We conducted a cross-sectional survey among 395 participants from the urban population of Kampala at Garden City Mall, Wandegeya market and Nakawa market 28th May - 7th June 2021. We asked about knowledge about organ donation and transplantation, collected sociodemographic data and did a sentiment analysis of participants' attitudes towards organ donation and transplantation. Results: The M:F ratio of participants was 1:1, majority (55.9%) of participants were Baganda, two thirds of participants knew about organ donation, 90% of participants did not know of any government policy on organ donation and transplantation. Radio/television was the commonest source of information. The commonest organ donated was the kidney. Overall, there were 94.3% and 93.2% positive sentiments towards organ transplantation and organ donation respectively. The need for stricter laws governing organ donation and transplantation, corruption and fear were the main negative sentiments expressed by participants. Conclusions: Sensitization of the community is required about government policy on organ donation and transplantation, and this should be communicated through radio/television and social media. There was a positive attitude towards organ donation and transplantation.
Keywords: Organ donation and transplantation; Low-income country; Urban population; Knowledge and attitude